Biotechnology law policy for developing countries: the third patentability requirement is still a constraint - Nor Ashikin Mohamed Yusof (Fakulti Undang - Undang, 2009)

(untitled)
Biotechnology either as a subject matter or invention and the act of patenting are relatively new to many developing countries. Biotechnological invention has limitless potentials. It is particularly important to pharmaceutical, medicinal, drug, chemicals, foods and agricultural industries worldwide. Developing countries could take advantage of the mandatory obligations of TRIPS as they have abundance of genetic resources. By supplying raw ingredients for biotechnology they may occupy the position of biotechnology producers globally. . This looks even brighter due to the current trend in patenting the same where the bar for non-obvious has been lowered drastically. This note explores on how the above current intellectual property trend and policy particularly in context of biotechnology law purportedly benefiting developing countries are putting constraints upon many of them instead. Firstly some background facts of TRIPS, which governs patent and is binding upon every country member domestically are presented. It then briefly explains biotechnology invention, the basic patentability requirements and the new trend of judicial courts in developed nations in interpreting the non-obvious requirement and reasons for doing so. Finally, the study will examine the disabilities of developing countries in overcoming even the much lowered standard of non-obvious requirement. This paper also points out that there are still many major tasks undone at national level which are hampering them from producing their first biotechnological invention or becoming active biotechnological producers